Comparative effectiveness and safety of tofacitinib vs. adalimumab in patients with rheumatoid arthritis: A systematic review and meta-analysis - Zhu, Chunyan; Zheng, Yibo; Wang, Zilu; Chen, Guozong; Li, Yushi (Frontiers in Pharmacology, 2025)
ObjectivesTo provide the latest systematic review and meta-analysis comparing the effectiveness and safety of tofacitinib and adalimumab in rheumatoid arthritis (RA) patients.MethodsA systematic search of PubMed, Embase, Web of Science, and Cochrane databases was conducted until April 2025. Randomized controlled trials and cohorts comparing tofacitinib and adalimumab in RA patients were included. Outcomes assessed were significant improvements in American College of Rheumatology (ACR) 20 improvement criteria, changes in visual analog scale (VAS) (global activity), disease activity score (DAS) 28-C-reactive protein (CRP), Health Assessment Questionnaire-Disability Index (HAQ-DI), and adverse events. Sensitivity analyses and subgroup analysis evaluated the robustness of results and heterogeneity. Data analysis was performed using Review Manager 5.4.1 and STATA 15.0.ResultsNine studies with 24,643 patients were analyzed. Tofacitinib showed superior effectiveness over adalimumab in ACR20 (risk ratio (RR): 1.28; 95% CI: 1.06, 1.55; P = 0.01), HAQ-DI (standardized mean difference (SMD): 0.20; 95% CI: 0.35, −0.05; P = 0.008), and VAS (SMD: 0.30; 95% CI: 0.56, −0.03; P = 0.03). No significant differences were found in adverse events (RR: 0.96; 95% CI: 0.89, 1.03; P = 0.22) or DSA28-CRP improvement (SMD: 0.02; 95% CI: 0.45, 0.02; P = 0.07). Sensitivity analyses confirmed stable outcomes for adverse events, HAQ-DI, and ACR20, but instability for VAS and DSA28-CRP. Subgroup analysis found that tofacitinib >5 mg twice daily was superior to ≤5 mg in terms of ACR20.ConclusionTofacitinib was more effective than adalimumab in improving ACR20, VAS, and HAQ-DI, with no significant differences in adverse events or DSA28-CRP improvement.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/.